2015
DOI: 10.15253/2175-6783.2015000300010
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated to the notification of congenital syphilis: an indicator of quality of prenatal care

Abstract: Objective: to analyze factors associated to the notification of congenital syphilis. Methods: a cross-sectional documentary,quantitative study, made through the National System of Notifiable Diseases. The study consisted of 113 notified cases. Adata collection form was used and Chi-square and Fisher tests were made. Results: women had prenatal exams (80.2%),serologic testing before six months of pregnancy (46.7%) and after (53.3%). There was an association for the variables race(p = 0.005) and serological test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
1
9
0
5
Order By: Relevance
“…Another hypothesis is related to the late treatment after a diagnosis obtained in hospital, whose criteria for treatment and notification are different from those used in primary healthcare. A study conducted in Northeast Brazil [23] demonstrates a high prevalence in the inadequate treatment of syphilis in pregnancy, which could explain the growing trends found in our study.…”
Section: Plos Onesupporting
confidence: 55%
“…Another hypothesis is related to the late treatment after a diagnosis obtained in hospital, whose criteria for treatment and notification are different from those used in primary healthcare. A study conducted in Northeast Brazil [23] demonstrates a high prevalence in the inadequate treatment of syphilis in pregnancy, which could explain the growing trends found in our study.…”
Section: Plos Onesupporting
confidence: 55%
“…1 The congenital form is currently considered a major public health challenge. The control strategy focuses on the prevention of the disease, which begins during prenatal care, with the early identification of maternal syphilis, through rapid syphilis tests and laboratory tests, which allows diagnosing pregnant women and their partners, and initiating treatment in a timely manner.. [1][2][3][4][5][6][7] Despite this, the incidence of the disease has increased progressively. [1][2][3] The incidence rate in Brazil for the years 2011, 2012 and 2013 were 3.3/1,000 live births; 4.0/1000 live births and 4.8/1000 live births, respectively.…”
mentioning
confidence: 99%
“…There is scientific evidence of the occurrence of congenital syphilis related to health service frailties regarding prenatal coverage and assistance in primary care. [4][5][6][7] In addition, maternal characteristics have also been associated with the occurrence of congenital syphilis. A national-based study identified the association of congenital syphilis cases in women aged 20 to 34 years, with lower levels of schooling, black skin color, no paid activity, late beginning of prenatal care, fewer visits and serological tests and inadequate treatment.…”
mentioning
confidence: 99%
“…Regarding the groups of women notified, in this study, the results portray a social profile of vulnerability. It is noted that the same characteristics are described in the literature: women with less education [9,11], mixed-race [5,6], urban residents [12] and housewives [13]. A study [12] shows that inequalities in access and prenatal quality are factors that contribute to the greater exposure of children from less privileged classes to the risk of vertical transmission of CS.…”
Section: Discussionmentioning
confidence: 73%
“…Other investigations [16,17] correlate the incidence of syphilis with women who became sexually active before the age of 19, with multiple partners, and who exhibit sexual behaviors that are vulnerable to sexually transmitted infections (STIs). It is considered that this age group is more prone to risky sexual behavior [12].…”
Section: Discussionmentioning
confidence: 99%